Impact of Digital Transformation on Efficiency and Profitability: BSI Islamic Bank 2022–2024 - Muhammad Adib Hasani (CV. Civiliza Publishing, 2026)
The rapid advancement of digital technology has reshaped the global banking industry, including Islamic banking, which faces unique challenges in balancing efficiency with ethical principles. This study investigates the impact of digital transformation on operational efficiency and profitability in Bank Syariah Indonesia (BSI) during 2022–2024. The purpose is to evaluate how technology investment and digital adoption influence cost structures and financial performance in the context of Islamic banking. Employing a descriptive quantitative approach with a case study design, the research utilizes secondary data from audited annual financial statements. The analysis focuses on three key indicators: operational efficiency measured by BOPO and Cost to Income Ratio (CIR), digitalization assessed through the growth of mobile banking transactions, and profitability evaluated via net profit. The findings reveal a significant escalation in technology investment, accompanied by rapid adoption of digital services and a marked shift in customer behavior toward electronic transactions. These developments contributed to a consistent decline in BOPO, stable CIR levels, and steady growth in net profit. From a theoretical perspective, digitalization not only enhances efficiency and reduces monitoring costs but also aligns with maqasid al-shariah by promoting resource optimization and financial inclusivity. In conclusion, digital transformation emerges as a strategic driver that strengthens competitiveness, supports sustainable growth, and reinforces the ethical foundation of Islamic banking.